2022
DOI: 10.3350/cmh.2022.0136
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of depression and anxiety in patients with hepatocellular carcinoma: Systematic review and meta-analysis

Abstract: Background:Depression and anxiety are associated with poorer outcomes in patients with hepatocellular carcinoma (HCC). However, the prevalence of depression and anxiety in HCC are unclear. We aimed to establish the prevalence of depression and anxiety in patients with HCC. Methods:MEDLINE and Embase were searched and original articles reporting prevalence of anxiety or depression in patients with HCC were included. A generalized linear mixed model with Clopper-Pearson intervals was used to obtain the pooled pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…18,19 A recent and extensive meta-analysis by Tan et al found that in 64 247 patients with HCC, one in four suffered from depression, while one in five suffered from anxiety. 20 In line with this, individuals with HCC suffer the third highest reported levels of psychological stress among people with the 14 leading cancers. 21 Despite this, the severe physical and psychosocial burden of liver disease is not addressed for patients with liver disease until late in the treatment course, near the terminal stage.…”
Section: Hepatocellular Carcinomamentioning
confidence: 82%
See 1 more Smart Citation
“…18,19 A recent and extensive meta-analysis by Tan et al found that in 64 247 patients with HCC, one in four suffered from depression, while one in five suffered from anxiety. 20 In line with this, individuals with HCC suffer the third highest reported levels of psychological stress among people with the 14 leading cancers. 21 Despite this, the severe physical and psychosocial burden of liver disease is not addressed for patients with liver disease until late in the treatment course, near the terminal stage.…”
Section: Hepatocellular Carcinomamentioning
confidence: 82%
“…When combined with HCC and its long and protracted treatment journey, patients with this typical dual presentation are subject to severe physical and psychological burden 18,19 . A recent and extensive meta‐analysis by Tan et al found that in 64 247 patients with HCC, one in four suffered from depression, while one in five suffered from anxiety 20 . In line with this, individuals with HCC suffer the third highest reported levels of psychological stress among people with the 14 leading cancers 21 .…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Notably, depression and anxiety are common in liver cancer patients, with a frequency about 25% and 20%, respectively [ 43 , 44 ]. These psychological illnesses and related symptoms have been reported to be associated with worse survival outcomes and quality of life for liver cancer patients and their family [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 The nature of the disease requires patients to adhere to specific lifestyle changes and treatment protocols. Regular monitoring and timely intervention are essential in managing cirrhosis and HCC, as well as providing emotional support, 3 which often requires a comprehensive understanding of the disease by patients. In light of this, an artificial intelligence (AI) model like GPT-4 can play a pivotal role in patient education, rendering detailed and accurate information on basic knowl-edge and disease management.…”
Section: Dear Editormentioning
confidence: 99%
“…The nature of the disease requires patients to adhere to specific lifestyle changes and treatment protocols. Regular monitoring and timely intervention are essential in managing cirrhosis and HCC, as well as providing emotional support [ 3 ]. which often requires a comprehensive understanding of the disease by patients.…”
mentioning
confidence: 99%